2008
DOI: 10.1103/physrevb.78.193104
|View full text |Cite
|
Sign up to set email alerts
|

Charge origin and localization at then-typeSrTiO3/LaAlO3interface

Abstract: We report a first-principles study of ͑LaAlO 3 ͒ m / ͑SrTiO 3 ͒ n heterostructures using density-functional theory at the LDA+ U level. Our results support the original explanation of Ohtomo and Hwang ͓Nature ͑London͒ 427, 423 ͑2004͔͒ that the charge at the n-type interface may be due to electrostatic doping. The internal electric field in the LaAlO 3 layer is calculated to be 0.24 V / Å. Though it is not sufficient to cause the dielectric breakdown in a wide band-gap La aluminate, it causes charge transfer in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
183
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(207 citation statements)
references
References 25 publications
23
183
1
Order By: Relevance
“…2(a) [36].) This behavior is consistent with the charge transfer mechanism known for the well-studied LaAlO 3 =SrTiO 3 system [9,37,38]. The charge transfer amounts to $0:16 electrons/interface Fe.…”
Section: Prl 107 166601 (2011) P H Y S I C a L R E V I E W L E T T Esupporting
confidence: 72%
“…2(a) [36].) This behavior is consistent with the charge transfer mechanism known for the well-studied LaAlO 3 =SrTiO 3 system [9,37,38]. The charge transfer amounts to $0:16 electrons/interface Fe.…”
Section: Prl 107 166601 (2011) P H Y S I C a L R E V I E W L E T T Esupporting
confidence: 72%
“…The discovery of a 2DEG (ref. 3) at the heterointerface between band insulators LaAlO 3 (LAO) and SrTiO 3 (STO) has launched many experimental [2][3][4][5][6][7][8][9][10][11][12]16 and theoretical 13,17,18 investigations of the fundamental origins and properties of this novel electronic state. Thiel et al 7 reported non-volatile electrical control of a metal-insulator quantum phase transition in LAO/STO heterointerface at room temperature.…”
mentioning
confidence: 99%
“…H eterointerfaces between different oxide layers can display remarkable electrical properties 1 that differ from either constituent, such as a two-dimensional electron gas (2DEG, refs [2][3][4][5][6][7][8][9][10][11][12][13][14] and interfacial superconductivity 15 . The discovery of a 2DEG (ref.…”
mentioning
confidence: 99%
“…Exploiting the flexibility of band modeling, we thus treat them as variable parameters to explore the phonondrag behavior in a range of different conditions. For what concern the 2DES thickness, ab-initio results 33,[63][64][65][66][67][68][69][70][71][72] show that for the charge density of interest (∼2-4×10 13 cm −2 ) the gas is entirely included in a few (∼2,3) d xy states confined in the TiO 2 layers closest to the interface, while only above ∼ 6×10 13 cm −2 the more extended d xz , d yz states sets in. However, in order to evaluate the scaling with respect to the 2D confinement, it is convenient to replace the actual squared wavefunctions with Gaussian envelope functions of variable thickness t (see Appendix-I for details).…”
Section: Phonon-drag Modelingmentioning
confidence: 99%